Integra????o regional e soberania: as muta????es do Estado Na????o no continente europeu - Ferreira, Celso Antonio Pires (2016)
The regional integration system that is based on the European Union was the result of a strong mutation in classical conceptual framework of the Nation. Sovereignty, according to the Westphalian???s concept began to be relaxed because of the internationalization of supranational rules based on cooperation between governments. In the European bloc, because of the economic crisis, it was found that the centralized political system in supranational entity began to be faced with structural problems of legitimacy, to be exercised by the States. These problems were consequences of the attempt of an economic and social planning within the European bloc. Experiment in which a reduction of economic imbalances have been made through paternalism, throughout the States economically stronger provide financial assistance during the integration process, the economically weaker countries. Such actions of social policy have proven insufficient to maintain economic stabilization block when member states are inserted in a recessionary environment. It was found that now, the States economically stronger tend to influence the decisions of the European block and remove the self-management capacity of the economically weaker states, leading to submission of central supranational decision models. In this process, a mutation in the interpretative content of the historical concept of sovereignty is unfolding. The difficulty of weak states in overcoming the economic crisis and internalize Community law produced by these supranational organisms has led to an ideology of resurgence of nationalist discourse. Authoritative this juncture, the danger of fragmentation of European unity can become a growing possibility.